Pengembangan Budidaya Sawi sebagai alternatif untuk Meningkatkan Ketahanan Pangan Masyarakat - Siarwi Siarwi; Adi Sofyana Latif; Yunus Nurhasan; Rananda Septanta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Food security remains a critical issue, particularly in urban areas where limited land availability restricts agricultural activities. One practical solution is the cultivation of fast-growing vegetables such as mustard greens (sawi), which can be grown in small spaces using simple techniques. This community service program aimed to enhance the knowledge and skills of local residents, especially women, in cultivating mustard greens as an alternative strategy to strengthen household food security. The program was conducted at Pamulang Permai Housing, West Pamulang, South Tangerang, on April 11, 2026. It was implemented by 10 lecturers from Pamulang University and involved 20 participants from the local PKK women’s group. The methods used included lectures, hands-on practice, discussions, and question-and-answer sessions. The implementation followed three main stages: preparation, execution, and reporting. The results indicated a significant improvement in participants’ understanding of mustard green cultivation techniques and their ability to apply these practices independently at home. Participants showed high enthusiasm during practical activities and demonstrated readiness to utilize limited yard space for food production. This activity contributed positively to increasing awareness of household-level food security and promoting sustainable urban farming practices.